Techniques and methods for winding the strings for the guitar - Luangkaew, Phatchara (Journal of Music and Performing Arts Khon Kaen University, 2023)
By this research, the researcher expects that Folk music and international music personnel or those who interested in creating music rehearsals be able to use the exercises that the researcher has created, and have an understanding of practice and apply correctly including understanding the theoretical content of both folk and international music together And hope that those who have studied this research document be able to apply knowledge, techniques, and strategies obtained from the research for the benefit of education, theory, for the development and as a guideline for the practice of folk and international music.